2022
DOI: 10.1039/d1ra08263a
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, electric and dielectric characterization of a NaCu0.2Fe0.3Mn0.5O2 compound

Abstract: The compound NaCu0.2Fe0.3Mn0.5O2 was synthesized using a solid-state method and it crystallized in a hexagonal system with a R3̄m space group in an O3-type phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…As a result, the complex polarizability is described as: where the real and imaginary components of the complex polarizability, respectively, are α ′ and α ′′ and ε is the complex dielectric constant. It is possible to determine the imaginary part of the complex polarizability parameter α ′′ using the relation given below: 81 …”
Section: Resultsmentioning
confidence: 99%
“…As a result, the complex polarizability is described as: where the real and imaginary components of the complex polarizability, respectively, are α ′ and α ′′ and ε is the complex dielectric constant. It is possible to determine the imaginary part of the complex polarizability parameter α ′′ using the relation given below: 81 …”
Section: Resultsmentioning
confidence: 99%
“… 26 In P3-NaFe 1/2 Mn 1/2 O 2 , the Na + ions occupy prismatic sites which share faces and edges with the surrounding MO 6 octahedra. 27 The atomic positions of each sample are illustrated in Table 1S † and the interatomic distances of Na–O and FeMn–O are portrayed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the compound Na 2/3 Fe 1/2 Mn 1/2 O 2 is a promising candidate compared to NaFe 1/2 Mn 1/2 O 2 for such applications. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that W M = 0.11 eV, which is equal to one quarter of activation energy (0.39 eV), proving that this model of CBH is ensured by a single polaron. 47 In the case of the single polaron correlated barrier jump model, the expression of AC conductivity is given by the following expression: [48][49][50] s ac ðoÞ ¼ where e 0 is the vacuum permittivity, e 0 is the dielectric constant of the material, N T is the number of state densities and U eff is the effective potential energy. Fig.…”
Section: C-namno 2 Phasementioning
confidence: 99%